Multiple Periodic Solutions of Delayed Predator-Prey Systems with Type IV Functional Responses on Time Scales - Shengbin Yu; Haihui Wu; Jiangbin Chen (Discrete Dynamics in Nature and Society)
With the help of a continuation theorem based on Gaines and Mawhin's coincidence degree, easily verifiable criteria are established for the existence of multiple positive periodic solutions of delayed predator-prey systems with type IV functional responses on time scales. Our results not only unify the existing ones but also widen the range of applications.